IMPROVEMENT OF PRACTICE OF ADULT PROTECTIVE SERVICES IN ARIZONA: IN-TAKE AND INVESTIGATION PROCESS REVIEW. (11th November 2018) - Sun, F; Kennedy, T
Abstract: Purpose: In order to improve consistency and fidelity of the Arizona Adult Protective Services (APS), this study examined APS process from intake, investigation, case planning to case closure and identified areas for improvement. Method: Two researchers independently reviewed 40 cases (Mage = 64.98) that were reported to APS in early 2017. Intake forms, recordings of telephone reports to Central Intake, investigation progress notes, and case information reports generated at case closure were critically examined. Results: Sample included 77.5% being non-Hispanic White, 35% living alone, 20% having dementia, and 10% having a prior history with APS. These characteristics were consistent with the total client population served in 2017. Inconsistency in completion of intake forms and the lack of connection of intake information and case planning were observed. Implications: Streamlining intake process (e.g., information gathering and documentation), incorporating intake information in case planning, and evaluating risk concerns at case closure were recommended.